The impact of information technology on the efficacy of tuition fee collection: a case in Jamaica. Issue 2 (17th February 2018) - Chevers, Delroy; Archie, Jonathon; Kerr-Gordon, Latoya; Hazel, Kerry
Abstract: Most governments in both developed and developing countries are reducing their financial support to universities. This condition is further compounded in Jamaica because the Jamaican government has shifted its focus and support from tertiary to early childhood education. As a result, both students and universities in Jamaica are experiencing financial difficulties. In an effort to overcome the challenges, one major university in the country has embarked upon a series of initiatives. These initiatives include, as a central element, the use of information technology (IT). Hence, this research seeks to answer the pivotal question, 'How does the use of information technology enable a Jamaican university to manage tuition fee collection in a manner that is effective yet sensitive to students' financial situation?' The survey found a significant relationship between the IT system and students being financially cleared at the release of examination results. In addition, the majority of students paid their tuition fees each semester via multiple payment options, and 64% of the Billing and Receivables staff believed that the IT system was effective in collecting tuition fees. These insights should assist universities' decision makers in identifying the best suite of financial strategies to enhance tuition fee collection.